Prognostic value of soluble programmed death-1 and soluble programmed death ligand-1 in severe traumatic brain injury patients - Lei Liu; Pengpeng Lan; Guiping Wu; Xiaojie Zhu; Hongfeng Shi; Yan Li; Ruili Li; Ling Zhao; Juan Xu; Min Xu (Scientific Reports)
Abstract Patients with traumatic brain injury (TBI) frequently exhibit concomitant immunosuppression. In this study, we evaluated the predictive values of soluble programmed death-1 (sPD-1) and soluble programmed death ligand-1 (sPD-L1) in patients with severe TBI. Peripheral blood sPD-1 and sPD-L1 levels were measured within 48 h of patient admission. A total of 20 healthy volunteers and 82 patients were enrolled in this study. The levels of sPD-1 and sPD-L1 were upregulated in patients with severe TBI (P < 0.001). They were significantly increased in the post-TBI severe pneumonia group and among non-survivors (P < 0.001). The area under the curves (AUCs) for sPD-1 and sPD-L1 levels to predict severe pneumonia were 0.714 and 0.696, respectively, and the AUCs to predict mortality were 0.758 and 0.735. The levels of sPD-1 and sPD-L1 are correlated with the GCS scores at admission, APACHE II scores, length of MV, and time elapsed to mortality. The levels of sPD-1 and sPD-L1 emerged as independent predictive factors for severe pneumonia and mortality. This study demonstrates that upregulation of sPD-1 and sPD-L1 in severe TBI patients is significantly associated with severe pneumonia and mortality, suggesting their potential as predictive biomarkers for these outcomes.